Rich-Club Organization Disturbances of the Individual Morphological Network in Subjective Cognitive Decline - Peng, Liling; Feng, Jing; Ma, Di; Xu, Xiaowen; Gao, Xin (Frontiers in Aging Neuroscience, 2022)
Background: Subjective cognitive decline (SCD) was considered to be the preclinical stage of Alzheimer’s disease (AD). However, little is known about the altered rich-club organizations of the morphological network in individuals with SCD. Methods: This study included 53 SCD individuals and 54 well-matched healthy controls (HC) from the ADNI database. Individual-level brain morphological networks were constructed by estimating the Jensen-Shannon distance-based similarity in the distribution of regional gray matter volume. Rich-club properties were then detected, followed by a statistical comparison. Results: The characteristic rich-club organization of morphological networks (normalized rich-club coefficients > 1) was observed for both the SCD and HC group under a range of thresholds. The SCD group showed a reduced normalized rich-club coefficient compared with the HC group. The SCD group exhibited the decreased strength and degree of rich-club connections than the HC group (strength: HC = 79.93, SCD = 74.37, p = 0.028; degree: HC = 85.28, SCD = 79.34, p = 0.027). Interestingly, the SCD group showed the increased strength of local connections than the HC group (strength: HC = 1982.16, SCD = 2003.38, p = 0.036). Conclusion: Rich-club organization disturbances of morphological networks in individuals with SCD reveal a distinct pattern between the rich club and peripheral regions. This altered rich-club organization pattern provides novel insights into the underlying mechanism of SCD and could be used to investigate prevention strategies at the preclinical stage of AD.